Changes in the incidence of periodontal pathogens during long-term monitoring and after application of antibacterial drugs - Janatová, T; Najmanová, L; Neubauerová, L; Kyselková, M; Novotná, G; Spízek, J; Janata, J; Dusková, J (Folia microbiologica, 2009)
The incidence of potential periodontal pathogens (Aggregatibacter actinomycetemcomitans, formerly Actinobacillus actinomycetemcomitans, Tannerella forsythia, Porphyromonas gingivalis, Prevotella nigrescens, Prevotella intermedia and Capnocytophaga ochracea) was monitored in patients with chronic periodontitis and in healthy control subjects. Two types of studies were carried out in which the composition of the bacterial communities in different niches of the same oral cavity ecosystem was investigated. Fluctuation or at least pronounced quantitative changes in the incidence of individual species in time were documented in the long-term study as well as after the local administration of antibacterial drug Chlo-Site or Metronidazole. Even within two weeks, a turnover of the monitored bacteria in separate niches of the oral biotope can be detected. A relatively high incidence of the tested periopathogens in the clinically healthy teeth of patients implies that even the "healthy" niches in the periodontal biotope function as a dynamic reservoir of periopathogenic microorganisms. This should be kept in mind when a local application of antibacterial compounds is used in the therapy of periodontal disease.
Keywords: gramnegativní bakteriální infekce; incidence; Adult; Case-Control Studies; monitorování léčiv; lidé středního věku; Gram-Negative Bacterial Infections; antibakteriální látky; Gram-Negative Bacteria; Periodontal Diseases; lidé; ústa; nemoci parodontu; mužské pohlaví; studie případů a kontrol; časové faktory; Anti-Bacterial Agents; dospělí; Mouth; Humans; Time Factors; Middle Aged; Male; gramnegativní bakterie; Drug Monitoring; Incidence